2022
DOI: 10.1155/2022/9365760
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Individual Herb of Mi-Jian-Chang-Pu Formula Exerts a Synergistic Effect in the Treatment of Ischemic Stroke in Rats

Abstract: Mi-Jian-Chang-Pu formula (MJCPF), composed of Crocus sativus L. and Acorus tatarinowii Schott, is a well-known TCM for treatment of hemiplegia, facial paralysis as well as language dysfunction caused by stroke both in ancient and modern times. By using pharmacodynamics, pharmacokinetics, and metabolomics, our present study discusses whether the combination of individual herbs or major active components of MJCPF possess synergistic neuroprotective effects against ischemic stroke (IS). 108 adult male Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…[27] It has been shown that Acori tatarinowii rhizoma decoction can reduce neurological deficits, lower levels of inflammatory factors, and improve consciousness disorders in acute cerebral infarction. [28,29]…”
Section: Effect In Seizure Tbi and Cerebrovascular Diseasementioning
confidence: 99%
“…[27] It has been shown that Acori tatarinowii rhizoma decoction can reduce neurological deficits, lower levels of inflammatory factors, and improve consciousness disorders in acute cerebral infarction. [28,29]…”
Section: Effect In Seizure Tbi and Cerebrovascular Diseasementioning
confidence: 99%